Inklusivitas dan Aksesibilitas dalam Alat Komunikasi Digital: Studi Kasus Platform Berbasis Peningkatan AI di Indonesia - Gemiharto, Ilham; CMS, Samson (Jurnal Pewarta Indonesia, 2024)
In the dynamic digital communication landscape, ensuring inclusivity and accessibility remains a pivotal concern. This qualitative case study explores contemporary challenges and inventive solutions within AI-enhanced platforms to champion digital communication that is all-encompassing. This research uses a qualitative case study methodology for various AI-enhanced digital communication tools. Comprehensive data was collected through in-depth interviews, content analysis, and usability assessments involving participants, including individuals with disabilities, accessibility experts, and digital communication tool developers. The study reveals significant hurdles in achieving inclusivity and accessibility, encompassing accessibility disparities for individuals with disabilities, limited awareness of accessibility features, and inherent design biases. It also unveils forward-looking strategies like AI-driven assistive technologies, voice-activated interfaces, and inclusive design principles that hold the potential to revolutionize digital communication. These findings underscore the pivotal role of inclusive design in AI-enhanced digital communication platforms, emphasizing the necessity for heightened awareness and collaboration among developers, accessibility experts, and users with disabilities. This research underscores the promising role of AI in mitigating accessibility challenges and advancing inclusivity. In pursuing all-encompassing and accessible digital communication, this qualitative case study provides valuable insights into the prevailing difficulties and pioneering pathways within AI-enhanced platforms. It calls for unified efforts among stakeholders to leverage AI's capabilities to render digital communication tools more inclusive, fostering a more equitable online environment